The “Pupil” Factory: Specialization and the Production of Human Capital in Schools - Fryer, Roland G. (American Economic Review, 2018)
I conducted a randomized field experiment in traditional public elementary schools in Houston, Texas designed to test the potential productivity benefits of teacher specialization. The average impact of encouraging schools to specialize their teachers on student achievement is −0.11 standard deviations per year on a combined index of math and reading test scores. I argue that the results are consistent with a model in which the benefits of specialization driven by sorting teachers into a subset of subjects based on comparative advantage is outweighed by inefficient pedagogy due to having fewer interactions with each student, though other mechanisms are possible. (JEL D31, E32, J22, J24, J31)